ROLE OF IMAGE IN MARKETING PERFORMANCE ODEL SUPPORTED BY MARKETING COMMUNICATION AND COMPANY SOCIAL RESPONSIBILITY - Eddy Soeryanto Soegoto (Jurnal Keuangan dan Perbankan, 2016)
AbstractBanking industries have not been effective yet in implementing marketing communication and company social responsibility programs. The establishment of image has not been done effectively yet; accordingly marketing performance cannot be implemented as it is expected. This research was done in the banking industries at Bandung City with sample as much as 42 banking industries drawn using a random sampling method. Thaanalysis procedure used Structural Equation Modeling based on Partial Least Square. This study generates anew model different with the previous researches where marketing communication and company social respon-sibility programs do not affect directly on the banking industries marketing performance. Nevertheless the image affect the marketing performance moderately. In conclusion, banking industries marketing perfor-mance can be maximal when the marketing communication is implemented effectively and the company social responsibility is implemented conducively in order to shape positive image.